Exploring the hospitality-tourism nexus: Directions and questions for past and future research. (March 2021) - Lugosi, Peter
Hospitality has often been conceived primarily as a supporting component of the tourism product. This commentary synthesises inter and multidisciplinary literature to examine alternative and more complex intersections of hospitality and tourism. It discusses four thematic areas of hospitality research: labour; the transformation of place (experiences); socio-material and socio-technological practice; and human encounters. It argues that applying hospitality as a sensitising concept in these domains of enquiry, and studying hospitality's abstract and concrete dimensions, enhances our understanding of tourism as socio-economic phenomena and a global system, and helps to appreciate tourism's implications for multiple stakeholders. Moreover, it proposes a range of questions for future research.